Ethnic boundary making institutions, power, networks - Wimmer, Andreas (New York ; Oxford : Oxford University Press, 2013)
Introducing a new comparative theory of ethnicity, Andreas Wimmer shows why ethnicity matters in certain societies and contexts but not in others, and why it is sometimes associated with inequality and exclusion, with political and public debate with closely-held identities, while in other cases ethnicity does not structure the allocation of resources, invites little political passion, and represent secondary aspects of individual identity.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ethnicity -- Political aspects; Boundaries -- Political aspects; Politics and culture; Ethnic barriers; Ethnic relations